AML-VAC-XS15-01: protocol of a first-in-human clinical trial to evaluate the safety, tolerability and preliminary efficacy of a multi-peptide vaccine based on leukemia stem cell antigens in acute myeloid leukemia patients - Jung, Susanne; Nelde, Annika; Maringer, Yacine; Denk, Monika; Zieschang, Lisa; Kammer, Christine; Özbek, Melek; Martus, Peter; Hackenbruch, Christopher; Englisch, Alexander; Heitmann, Jonas S.; Salih, Helmut R.; et al. (Frontiers in Oncology, 2024)
IntroductionAcute myeloid leukemia (AML) has a dismal prognosis, mostly due to minimal residual disease-driven relapse, making an elimination of persisting therapy-resistant leukemia progenitor/stem cells (LPCs) the main goal for novel therapies. Peptide-based immunotherapy offers a low-side-effect approach aiming to induce T cell responses directed against human leukocyte antigen (HLA) presented tumor antigens on malignant cells by therapeutic vaccination. Mass spectrometry-based analysis of the naturally presented immunopeptidome of primary enriched LPC and AML samples enabled the selection of antigens exclusively expressed on LPC/AML cells, which showed de novo induction and spontaneous memory T cell responses in AML patients, and whose presentation and memory T cell recognition was associated with improved disease outcome.MethodsBased on these data the therapeutic vaccine AML-VAC-XS15 was designed, comprising two mutated HLA class I-restricted peptides from the common AML-specific mutation in NPM1 and seven HLA class II-restricted peptides (six non-mutated high-frequent AML/LPC-associated antigens and one mutated peptide from the AML-specific mutation R140Q in IDH2), adjuvanted with the toll like receptor 1/2 ligand XS15 and emulsified in Montanide ISA 51 VG. A phase I open label clinical trial investigating AML-VAC-XS15 was designed, recruiting AML patients in complete cytological remission (CR) or CR with incomplete blood count recovery. Patients are vaccinated twice with a six-week interval, with an optional booster vaccination four months after 2nd vaccination, and are then followed up for two years. The trial’s primary objectives are the assessment of the vaccine’s immunogenicity, safety and toxicity, secondary objectives include characterization of vaccine-induced T cell responses and assessment of preliminary clinical efficacy.Ethics and disseminationThe AML-VAC-XS15-01 study was approved by the Ethics Committee of the Bavarian State medical association and the Paul-Ehrlich Institut (P01392). Clinical trial results will be published in peer-reviewed journals.